Pregunta
upstudy study bank question image url

derivative of the function \( H(x)=\frac{\sqrt{x^{2}-3}}{\left(x^{2}+7\right)^{2}} \)

Ask by Simpson Gray. in the United States
Feb 22,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

The derivative of \( H(x) \) is \( H′(x) = \frac{x(19 - 3x²)}{(x² + 7)^3 \sqrt{x² - 3}} \).

Solución

We wish to differentiate   H(x) = (√(x² − 3))⁄((x² + 7)²). Step 1. Write Numerator and Denominator.  Let   u(x) = √(x² − 3) = (x² − 3)^(1/2),   v(x) = (x² + 7)². Then, H(x) = u(x)/v(x). Step 2. Compute u′(x). Using the chain rule,   u′(x) = (1/2)(x² − 3)^(−1/2) · (2x) = x/√(x² − 3). Step 3. Compute v′(x). Since v(x) = (x² + 7)², we get   v′(x) = 2(x² + 7) · (2x) = 4x(x² + 7). Step 4. Apply the Quotient Rule. Recall the quotient rule:   H′(x) = [u′(x)v(x) − u(x)v′(x)] / [v(x)]². Plug in u, u′, v, and v′:   H′(x) = { [x/√(x² − 3)]·(x² + 7)² − √(x² − 3)·[4x(x² + 7)] } / [ (x² + 7)⁴ ]. Step 5. Simplify the Expression. Factor common terms in the numerator:  Both terms have an x and at least one factor of (x² + 7). Write:   Numerator = x(x² + 7) { (x² + 7)/√(x² − 3) − 4√(x² − 3) }. Thus,   H′(x) = x(x² + 7) { (x² + 7)/√(x² − 3) − 4√(x² − 3) } / (x² + 7)⁴ = x { (x² + 7)/√(x² − 3) − 4√(x² − 3) } / (x² + 7)³. We can combine the terms in curly brackets over a common denominator √(x² − 3):   (x² + 7)/√(x² − 3) − 4√(x² − 3) = [ (x² + 7) − 4(x² − 3) ] / √(x² − 3). Compute the numerator:   (x² + 7) − 4(x² − 3) = x² + 7 − 4x² + 12 = −3x² + 19. Thus, the derivative becomes:   H′(x) = [ x(−3x² + 19) ] / [ (x² + 7)³ √(x² − 3) ]. Step 6. Write the Final Answer. The derivative of the function H(x) is   H′(x) = x(19 − 3x²)⁄[(x² + 7)³ √(x² − 3)]  . (Notice that −3x² + 19 = 19 − 3x².)

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

Extra Insights

To find the derivative of the function \( H(x)=\frac{\sqrt{x^{2}-3}}{\left(x^{2}+7\right)^{2}} \), we will use the quotient rule, which states that if you have a function of the form \( \frac{u}{v} \), then its derivative \( H'(x) \) is given by: \[ H'(x) = \frac{u'v - uv'}{v^2} \] Here, \( u = \sqrt{x^2 - 3} \) and \( v = (x^2 + 7)^2 \). 1. First, find \( u' \): \[ u' = \frac{1}{2\sqrt{x^2 - 3}} \cdot 2x = \frac{x}{\sqrt{x^2 - 3}} \] 2. Next, find \( v' \): \[ v = (x^2 + 7)^2 \implies v' = 2(x^2 + 7) \cdot 2x = 4x(x^2 + 7) \] 3. Now, apply the quotient rule: \[ H'(x) = \frac{\left(\frac{x}{\sqrt{x^2 - 3}}\right)(x^2 + 7)^2 - \sqrt{x^2 - 3}(4x(x^2 + 7)}{(x^2 + 7)^4} \] 4. Simplifying gives: \[ H'(x) = \frac{x(x^2 + 7)^2 - 4x(x^2 - 3)(x^2 + 7)}{(x^2 + 7)^4 \sqrt{x^2 - 3}} \] This is the derivative of the function \( H(x) \).

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad